Wage differentials by firm size: the efficiency wage test in a developing country - Tatiane Almeida de Menezes (Universidade de São Paulo, 2014)
Using data from the Brazilian Labor Monthly Survey (PME/ IBGE) for the years of 2006 and 2007, the paper investigates if the wage differential by firm size in a developing country, such as Brazil, can be explained by the predictions of the Efficiency Wage Theory. It is adopted a Switching Regression Model to estimate if large size companies pay a higher wage premium for dispended labor effort, as compared to smaller enterprises. The results prove the EW predictions since they evidence positive relationships between wages and labor effort, schooling and longer job duration. However, such findings are not sufficient to explain the existence of wage differentials by firm size in the Brazilian labor market.